Effects of rice husk nanosilica on color stability of metal-ceramic crowns - Sinamo, Sopan; Martono, Martono; Ginting, Deva Yani Br; Davin, Davin; Azzanjani, Aisyah Bella; Hadi, Lina; Hasim, Bryan Julio; Watri, Desi; Chiuman, Veranyca (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Metal-ceramic crowns remain a primary choice for dental restoration due to their adequate mechanical strength and relatively low cost. However, their esthetic success depends on the color stability of the porcelain, particularly the opaque layer that masks the underlying metal. Nanosilica derived from rice husks is an environmentally friendly material with potential as a reinforcing agent, but data on its effect on color changes in metal-ceramic crowns remain limited. This study aimed to analyze the effect of adding 0.5% rice husk nanosilica to the opaque layer on color changes in metal-ceramic crowns. Methods: An in vitro experimental study used Co-Cr metal samples coated with porcelain, with color evaluation based on the CIELAB system (L*, a*, b*) via colorimeter before and after nanosilica addition. Nanosilica was synthesized from rice husks and characterized using particle size analysis and scanning electron microscopy. Data were analyzed with Shapiro-Wilk test, Levene test, Welch t-test, and paired t-test. Results: Characterization results showed nanosilica particles in the nanoscale range with two main distribution peaks and amorphous, spherical morphology with agglomeration tendency. L* values increased significantly, whereas changes in a* and b* values showed no significant differences. Conclusion: These findings indicate that adding 0.5% rice husk nanosilica to the opaque layer increases brightness and total color change in metal-ceramic crowns, requiring esthetic control in its application.